وحی و نبوت اور مغربی مصنفین : منٹگمری واٹ اور رابرٹ سپنسر کی آرا کا تقابلی جائزہ (Al-Qamar, 2024)
It is an undeniable truth that the channel through which revelation became known to humankind is prophethood. Both revelation and prophethood are thus intertwined; the explanation of one will remain wanting without reference to the other. But majority of the Orientalists have tried their best to criticize and accuse Qur’anic revelation with a lot of misconceptions and allegations concerning wahy since dawn. So, this paper tries to find out the Orientalists view and concept on wahy based on the writings of western scholars. This paper gives high focus on analyzing their concepts and views related the issue and to answer and rectify the misconceptions describing the real facts and teaching of Islam in the issue related to wahy. So, this paper will be helpful to establish fact on Qur’anic revelation to the Prophet. Like other Orientalists, William Montgomery watt and Robert Spencer have actually denied Islamic scholars views about revelation and Prophet hood in their Qur’an commentaries. In this paper, an effort has been made to examine the arguments of both western scholars and to deduce the actual position about this topic. In this research written with a descriptive, comparative and analytical approach, it is proved that according to Quran, sciences of Tafsir and Hadith literature, history and logic, the explicit concepts of both scholars about revelation of the Prophet Muhammad (PBUH) are baseless and have been rejected with the arguments given by the majority of the Muslim scholars and thinkers.
Keywords: Revelation; Prophethood; Qur’an; Watt; Spencer; Orientalists